2007
DOI: 10.1645/ge-945r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aestivation and Starvation on the Neutral Lipid and Phospholipid Content of Biomphalaria Glabrata Infected With Schistosoma Mansoni

Abstract: The effects of aestivation or starvation on the neutral lipid and phospholipid content of Biomphalaria glabrata patently infected with Schistosoma mansoni were determined by high-performance thin-layer chromatography-densitometry. Infected-aestivated snails were maintained in a moist chamber at 24 +/- 1 C and a relative humidity of 98 +/- 1%. Infected-starved snails were maintained in artificial spring water (ASW) at 23 +/- 1 C without exogenous food. Infected snails (the controls) were maintained in ASW at 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Our results are consistent with fecundity compensation because the prolonged fitness and persistence of this parasite relies on the survival of its host, and aestivation presents high mortality risk for both the host and the parasite (White et al. ; Studer et al. ; Rubaba et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are consistent with fecundity compensation because the prolonged fitness and persistence of this parasite relies on the survival of its host, and aestivation presents high mortality risk for both the host and the parasite (White et al. ; Studer et al. ; Rubaba et al.…”
Section: Discussionsupporting
confidence: 89%
“…Although some infected snails are able to survive this process, aestivation combined with infection does greatly increase mortality in snail populations and the likelihood of death for individual snails (White et al. ; Rubaba et al. ).…”
mentioning
confidence: 99%
“…It is well established that several schistosome intermediate host species (including B. truncatus ) have the ability to aestivate [46]. It has been demonstrated that aestivation negatively affects the survival of infected snails [47, 48]. In our experiments cold temperatures did not affect B. truncatus snails, regardless of their infection status.…”
Section: Discussionsupporting
confidence: 44%
“…Metabolomic analysis of snails following miracidial infection has shown that malic acid and other carboxylic acids are important biomarkers for detecting S. mansoni at different stages of infection in the hemolymph and digestive glands of Biomphalaria alexandrina (330). Changes in lipid levels and concentrations of metabolic by-products, such as pyruvic acid, fumaric acid, and malic acid, in the digestive gland gonad complex of B. glabrata snails infected with S. mansoni have also been identified (331,332). Although the latter approaches are important for understanding the biology of intermediate hosts infected with schistosomes, their application in detecting infection would be limited due to their nonspecificity and the extensive technology required to undertake the analysis.…”
Section: Detection Of Infected Intermediate Snail Hostsmentioning
confidence: 99%